Communication, Social Norms, and the Intention to Get Vaccinated Against Covid-19 - Sarah Geber; Shirley S. Ho; Mengxue Ou (University of Zurich, IKMZ - Department of Communication and Media Research, 2023)
Social norms are a promising factor for pandemic control, as they motivate people to engage in preventive behaviours. However, little is known about the influence of perceived social norms on the intention to get vaccinated against Covid-19 and the role of communication in shaping such normative perceptions. Moreover, despite the pandemic's global scale, a cross-cultural perspective is scant in research on Covid-19 preventive behaviour. The present study examined the relationships between communication (i.e., attention to mass media and social media), social norms (i.e., perceived norms in the population and personal environment), and people's intention to get vaccinated against Covid-19 using a cross-national survey in Singapore (N = 998) and Switzerland (N = 1,022). Multigroup structural equation modelling revealed that attention to mass media was positively correlated with perceived norms in both countries, whereas attention to social media was correlated with normative perceptions only in Singapore. Normative perceptions regarding the population and personal environment were positively correlated with vaccination intention in Singapore. However, in Switzerland, only perceived norms in the personal environment were positively related to vaccination intention. The results are discussed against the background of both countries' media systems and cultural values (i.e., individualism/collectivism) and are instructive for norms-based interventions in times of crises.